2019
DOI: 10.18632/oncotarget.27334
|View full text |Cite
|
Sign up to set email alerts
|

Analog-sensitive cell line identifies cellular substrates of CDK9

Abstract: Transcriptional cyclin-dependent kinases regulate all phases of transcription. Cyclin-dependent kinase 9 (CDK9) has been implicated in the regulation of promoter-proximal pausing of RNA polymerase II and more recently in transcription termination. Study of the substrates of CDK9 has mostly been limited to in vitro approaches that lack a quantitative assessment of CDK9 activity. Here we analyzed the cellular phosphoproteome upon inhibition of CDK9 by combining analog-sensitive kinase technology with quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 45 publications
(50 reference statements)
1
23
0
Order By: Relevance
“…Among them is transcription termination factor Xrm2, suggesting that P-TEFb is also involved in the regulation of transcription termination, which is consistent with the observation by Kouzarides and colleagues that aberrant stimulation of P-TEFb activity results in global transcriptional readthrough in ES cells [114]. Interestingly, another HTS search using an analogue-sensitive CDK9 mutant followed by mass spectrometry (MS) conducted by Eick and colleagues identified putative CDK9 substrates that showed a minimum overlap with the putative substrates identified by the Fisher group [113,115]. Further studies are required to complete the list of CDK9 substrates in cells.…”
Section: Substrates Of Cdk9supporting
confidence: 82%
“…Among them is transcription termination factor Xrm2, suggesting that P-TEFb is also involved in the regulation of transcription termination, which is consistent with the observation by Kouzarides and colleagues that aberrant stimulation of P-TEFb activity results in global transcriptional readthrough in ES cells [114]. Interestingly, another HTS search using an analogue-sensitive CDK9 mutant followed by mass spectrometry (MS) conducted by Eick and colleagues identified putative CDK9 substrates that showed a minimum overlap with the putative substrates identified by the Fisher group [113,115]. Further studies are required to complete the list of CDK9 substrates in cells.…”
Section: Substrates Of Cdk9supporting
confidence: 82%
“…Crystal structures of the complex have been determined (Baumli et al 2008;Tahirov et al 2010), which reveal an organization and interfaces common among CDK:Cyclin pairs but also distinct features. Substrates for the CDK9 kinase have been identified from proteomics experiments in human cell extracts (Sansó et al 2016) or from analog-sensitive cell lines (Decker et al 2019). These studies revealed dozens of high-confidence targets, with many representing transcription cofactors or RNA processing factors.…”
Section: P-tefbmentioning
confidence: 99%
“…Comparison of CDK7 phosphosites with those from other transcription-associated kinases CDK8/CDK19 (Poss et al 2016), CDK9 (Sansó et al 2016;Decker et al 2019), and CDK12/CDK13 (Krajewska et al 2019) revealed few B A C Figure 2. SILAC phosphoproteomic overview and identification of phosphorylation sites significantly changed by SY-351 treatment.…”
Section: Sy-351: a Potent Highly Selective Covalent Cdk7 Inhibitormentioning
confidence: 99%